2021
DOI: 10.3389/fmed.2021.760047
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 and ChAdOx1 SARS-CoV-2 Post-vaccination Side-Effects Among Saudi Vaccinees

Abstract: Background: Vaccination against SARS-CoV-2 is important for reducing hospitalization and mortalities. Both Pfizer-BioNTech (BNT162b2) and the Oxford-AstraZeneca (ChAdOx1 nCoV-19) vaccines are used in Saudi Arabia and in many parts of the world. Post-vaccinal side effects were recorded, so we aimed to screen different complaints after vaccination among vaccinees in Saudi Arabia.Methods: An online questionnaire was designed to screen the local, systemic, and allergic post vaccination reactions for vaccinees who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
73
5
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 37 publications
20
73
5
2
Order By: Relevance
“…Moreover, those participants were more likely to experience post-vaccination side effects with moderate to severe levels. These findings support the results of a study from Saudi Arabia by Alghamdi et al, which showed that the presence of chronic diseases correlated with the development of post-vaccination side effects [ 84 ]. Moreover, smokers were more susceptible to experience sweating for no reason, whereas non-smokers were more susceptible to experience injection site pain and swelling.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, those participants were more likely to experience post-vaccination side effects with moderate to severe levels. These findings support the results of a study from Saudi Arabia by Alghamdi et al, which showed that the presence of chronic diseases correlated with the development of post-vaccination side effects [ 84 ]. Moreover, smokers were more susceptible to experience sweating for no reason, whereas non-smokers were more susceptible to experience injection site pain and swelling.…”
Section: Discussionsupporting
confidence: 91%
“…The BNT162b2 (Pfizer-BioNTech) statistics of side effects are contrasting. An ongoing multinational placebo-controlled clinical trial reported 27% ( 34 ), but surveys with self-reported symptoms showed figures between 80 and 92% ( 21 , 22 , 35 ). Ad5-nCoV (CanSinoBIO) and Ad26.CoV2.S (Johnson & Johnson/Janssen) frequencies were close to the ones reported in phase 2 clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Both were within the range of self-report surveys. The former has shown prevalence ranging from 51 to 96% ( 21 , 27 , 35 , 38 , 39 ) and the second one, prevalence ranging from 71 to 82% ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some patients might already have an underlying illness that can cause thrombosis regardless of COVID-19 or COVID-19 vaccination [ 24 ]. Some recent Arabic reports showed that the incidence of thrombocytopenia and peculiar thrombotic events might be more common in viral vector technology based COVID-19 vaccine [ 25 , 26 ]. According to the recent management recommendation, mass COVID-19 vaccination should continue but with special caution [ 27 ].…”
Section: Pathophysiology Of Thrombotic Disorder and Problem In Covid-19/covid-19 Vaccinationmentioning
confidence: 99%